PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN THE PLAZA RESIDENCES - Angel Nainggolan; Paul Eduard Sudjiman (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
This study aims to determine the effect of motivation and work discipline on employee productivity at The Plaza Residence, either partially or simultaneously. The population in this study were all employees at The Plaza Residence with a total of 111 employees and a sample of 70 respondents. The technique used in this research is to distribute online questionnaires using google form. The analysis used is descriptive statistics analysis, validity and reliability test, determination coefficient test, t test, and F test. Judging from the coefficient of determination test, it is found that there is a strong relationship between motivation, work discipline and work productivity. The results of the t test, the motivation variable partially has no significant effect on work productivity, but the work discipline variable partially has a significant effect on work productivity. If viewed from the F test shows that the variables of motivation and work discipline simultaneously have a significant effect on productivity.